COMPARISON OF LOADING DOSE OF CLOPIDOGREL WITH TICAGRELOR IN ELDERLY PATIENTS UNDERGOING PCI IN STABLE ISCHEMIC HEART DISEASE - AKHUND , N; SHIREEN, DR; MALIK , Z; JAMIL , W (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to compare the efficacy and safety of loading doses of clopidogrel with ticagrelor in elderly patients undergoing PCI in SIHD. Methods: A randomized controlled trial was conducted at Saidu Group of Teaching Hospitals from January 2019 to January 2020. 600 patients aged 65 years or older with SIHD who underwent PCI were randomized to receive either a loading dose of clopidogrel 600mg or ticagrelor 180mg. The primary endpoint was a composite of death, myocardial infarction, stent thrombosis, or stroke at 30 days post-PCI.Results: The incidence of the primary endpoint was similar in both groups (8.3% in the clopidogrel group vs. 8.2% in the ticagrelor group, P=0.95). There were no significant differences in the rates of individual components of the primary endpoint between the two groups. Bleeding events were also similar in both groups (4.8% in the clopidogrel group vs. 4.7% in the ticagrelor group, P=0.95). However, ticagrelor was associated with a significantly higher incidence of dyspnea (9.8% vs. 2.3%, P<0.001).Conclusion: In elderly patients undergoing PCI for SIHD, a loading dose of clopidogrel was found to be non-inferior to ticagrelor in terms of the composite endpoint of death, myocardial infarction, stent thrombosis, or stroke at 30 days post-PCI.